The Effect Of Mental Health Screening Training On The Level Of Knowledge About Mental Disorders In 4th Semester Students Of The Bachelor Of Nursing - Erik Adik Putra Bambang Kurniawan; Marita Kumala Dewi (Sahabat Publikasi Kuu, 2025)
Background: Mental health is a condition when someone feels healthy and happy, able to face life's challenges and can accept others as they should and have a positive attitude towards themselves and others. Mental health is no longer just discussing the problem of mental disorders, but healthy and risk groups also need to be known so that the community gets the right action, one of which is mental health in students. Various studies show that the level of knowledge in students is still very lacking about mental health. There needs to be mental health screening training to be able to improve understanding and knowledge related to mental disorders. Objective: To determine the effect of mental health screening training on the level of knowledge about mental disorders in fourth semester students of the Bachelor of Nursing Study Program. Method: This study uses a quasi-experimental research method. Research Results: The results of the Wilcoxon test showed Asymp. Sig (2-tailed) at the stress level is 0.000. Because the P value <α: 0.05, then Hα is accepted and Hο is rejected. Conclusion: There is an effect of mental health screening training on the level of knowledge about mental disorders in fourth semester students of the Bachelor of Nursing Study Program. Suggestion: Further researchers are expected to develop this research, and are expected to re-examine the factors that influence the level of knowledge about mental disorders in students.